2013
DOI: 10.5717/jenb.2013.17.4.161
|View full text |Cite
|
Sign up to set email alerts
|

The estimation of mineral contents in oriental supplements consumed by elite athletes

Abstract: The purpose of this study is twofold: to examine macro (calcium, magnesium, and phosphorus) and trace mineral (iron) concentration in oriental supplements (OS), and to define OS prevalence in elite athletes. Participants of this study were 928 varsity athletes (male: 680, female: 248) with 23 sports types. Recent 3-month dietary supplements (DS) and OS practice was surveyed during training period, and mineral concentration in 72 randomly collected OS samples were analyzed. DS use was 41% and OS use was 20% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…56,57 Ayrıca sporcularda saçın segmental analizi tekli idrar analizinin aksine, ilaç veya madde kullanımının sıklığını ve geçmi-şini, tekrarlayan kötüye kullanımları gösterebil-mektedir. 58 Emre MUTLU ve ark.…”
Section: Dopi̇ng Uygulamalarinin Doğrulanmasiunclassified
“…56,57 Ayrıca sporcularda saçın segmental analizi tekli idrar analizinin aksine, ilaç veya madde kullanımının sıklığını ve geçmi-şini, tekrarlayan kötüye kullanımları gösterebil-mektedir. 58 Emre MUTLU ve ark.…”
Section: Dopi̇ng Uygulamalarinin Doğrulanmasiunclassified
“…The midfoot functions as a shock absorber in the plantar portion, while it allows the foot arch to maintain appropriate elasticity in order to reduce the impact of the ground reaction force (GRF). Constant impact on the plantar aspect by the GRF increases the occurrence of injuries such as heel pain, pelvic malalignment, and plantar fasciitis [6]. Previous studies have identified that functional disorders in the foot could cause lower back, hip, knee, and ankle joint injuries [7, 8].…”
Section: Introductionmentioning
confidence: 99%